Obturator Nerve Injury: An Infrequent Complication of TOT Procedure - S. Aydogmus; S. Kelekci; H. Aydogmus; E. Ekmekci; Y. Secil; S. Ture (Hindawi Limited, 2014)
Transvaginal mid-urethral slings have become the most preferred surgical treatment option for female stress urinary incontinence. However, various complications have been reported for these operations occurring especially during penetration of the retropubic space. It can negatively affect patient's quality of life. Early treatment increases the chance of complete normalization of the functions. In this case report we presented a case of obturator nerve damage that was diagnosed and treated at early stage after TOT operation.